Sistem Akuntansi Pembeli Bahan Baku Pada CV. Lautan Ilmu Medan - Agnes Sulvianty Tarigan (MTU PRESS, 2022)
The purpose of writing this final project is to find out whether the purchasing system of CV. Lautan Ilmu Medan is good, namely by describing the raw material purchasing system. CV purchasing system data. Lautan Ilmu Medan is obtained from the results of observations, interviews and documentation of data collected by qualitative discriminatory techniques. The results of the data indicate that the raw material purchasing system has been implemented quite well because it involves functions with their respective duties and responsibilities.